The Implementation of Context, Input, Process, Product Evaluation Model for Assessing Educational Programs - Nurhasanah, Enung; Ratnaya, I Gede; Agung Parwata, I Gusti Lanang; Made Budhyana, I Dewa Ayu (JETAL: Journal of English Teaching & Applied Linguistic, 2025)
The objective of this study is to undertake a critical examination of the implementation of the CIPP (Context, Input, Process, Product) evaluation model in junior high school educational programs. This examination will be facilitated through a systematic review of 51 studies published between 2015 and 2024. Utilizing a systematic literature review (SLR) approach, this research explores the application contexts, theoretical frameworks, scholarly debates, as well as the practical implications and limitations of using the CIPP model across various educational sectors. The present study utilizes a primary instrument in the form of a data categorization checklist based on the four components of the CIPP model. The data were collected through systematic access to digital journal databases, such as Scopus, with articles filtered based on specific keywords according to inclusion criteria. The selection of articles was conducted in accordance with the PRISMA flow, encompassing the phases of identification, screening, eligibility assessment, and final inclusion. Thematic analysis was employed to code and interpret the content of the selected studies, with a focus on the type of program, evaluation approach, CIPP dimensions analyzed, and key findings. The findings indicate that the CIPP model has been extensively adopted due to its comprehensive and adaptable structure, which effectively assesses the planning, execution, and outcomes of educational programs. The integration of authentic assessment and competency-based learning is a common practice, as it aligns with specific contextual needs. However, the review also identifies key limitations, including the predominance of quantitative methods, uneven geographic distribution of studies, and limited exploration of technology integration.